2021
DOI: 10.1111/vsu.13629
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a surgical checklist on surgical outcomes in an academic institution

Abstract: Objective: To determine the influence of a surgical checklist (SC) on morbidities and compliance with safety measures. Study Design: Before-and-after-intervention study.Sample Population: Three thousand two hundred eighty-six dogs: 1375 dogs pre-SC and 1911 post-SC.Methods: Completion of safety measures and occurrence of morbidity and/or mortality during hospitalization and up to death or 30-days postoperatively were recorded.Results: Safety measures were more frequently completed post-SC, including oral confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Bergström et al 15 found that SSC introduction reduced complication rates from 17% (pre-use) to 7% when SSCs were used in a university hospital setting. Most other single-site studies [16][17][18][19] report similar findings. Therefore, SSC use is supported and promoted as part of the quality improvement and clinical governance process to optimise veterinary patient safety and wellbeing.…”
Section: Introductionsupporting
confidence: 69%
“…Bergström et al 15 found that SSC introduction reduced complication rates from 17% (pre-use) to 7% when SSCs were used in a university hospital setting. Most other single-site studies [16][17][18][19] report similar findings. Therefore, SSC use is supported and promoted as part of the quality improvement and clinical governance process to optimise veterinary patient safety and wellbeing.…”
Section: Introductionsupporting
confidence: 69%
“…8,11 Modification of the WHO SSC for veterinary use has resulted in similar improvements in patient outcomes. [12][13][14][15][16] Improvements associated with use of a SSC have included decreased rates of surgical site infection, fewer wound healing complications, and improved perioperative antimicrobial prophylaxis. 12,[14][15][16] However, these findings have generally presumed a high SSC completion rate, and may not be reflective of long-term clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Improvements associated with use of a SSC have included decreased rates of surgical site infection, fewer wound healing complications, and improved perioperative antimicrobial prophylaxis. 12,[14][15][16] However, these findings have generally presumed a high SSC completion rate, and may not be reflective of long-term clinical use. More recently, challenges associated with successful veterinary SSC implementation have been described.…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, customising checklists according to the procedure being performed has also been demonstrated to have benefits beyond increased completion of safety measures, with their use reported to decrease unexpected returns to surgery and reduce anaesthetic duration. 10 However, the usefulness of checklists in veterinary medicine doesn't end at reducing surgical complications. Indeed, checklists have now been devised to aid in improving veterinary healthcare across subjects ranging from the detection of osteoarthritis in cats 11 to increasing…”
mentioning
confidence: 99%
“…For example, complication rates for permanent transvenous pacemaker implantation in dogs reduced from 16.6 per cent to 2.2 per cent when a customised checklist was used, 8 while surgical site infection rates following coeliotomy for gastrointestinal foreign body removal reduced from 19.9 per cent to 11.9 per cent when using a checklist specifically developed for the procedure 9 . Furthermore, customising checklists according to the procedure being performed has also been demonstrated to have benefits beyond increased completion of safety measures, with their use reported to decrease unexpected returns to surgery and reduce anaesthetic duration 10 …”
mentioning
confidence: 99%